التأثيراتُ العربيَّةُ الإسلاميَّةُ على إفريقيا الإسلاميَّةِ (جنوبِ الصحراءِ) في الجانبِ العمرانيِّ (Journal of Academic Research, 2025)
This study examines the impact of Muslims on the Islamic kingdoms of sub-Saharan Africa from an architectural and urban development perspective. The spread of Islam contributed to significant architectural transformations, manifested in the construction of mosques, the planning of cities, and the establishment of educational and religious centers. These developments reflect the interaction between Islamic culture and the local environment, with reference to prominent Islamic figures who played a role in this architectural renaissance.The research will adopt the historical method by tracing and interpreting events and developments based on reliable historical sources, in order to understand the evolution of urbanism in these kingdoms within their temporal and cultural context.